India's pathway through financial crisis - Arunabha Ghosh (University of Oxford, Global Economic Governance Programme (GEG), 2004)
India survived near-crisis situations twice in the 1990s. What determined its ability to learn from the experience of a balance of payments crisis in 1991 to shield the economy from the pressures of the Asian financial crisis in 1997? By linking the two crises within a framework of external and internal economic and political constraints, the paper explains the dynamics of the crises. It argues that India's success can be attributed to five sets of decisions taken during 1991-97: devaluation, engaging the IMF, floating the exchange rate while increasing the central bank's autonomy to intervene against speculative pressures, opening up the external sector while maintaining asymmetric capital controls, and liberalising the financial sector. The paper analyses the options, political opposition and eventual outcomes for each set of decisions. Based on this approach it argues that India's ownership of its reform programme helped set the pace of reform while close interaction between technocrats and the IMF added credibility. But the balance between entrenched traditional interest groups and the demands of new interests determined the scope of reform. Finally, the paper raises broad political questions for the lessons other countries can draw from India's experience.
Keywords: 330